Value of the Resting Electrocardiogram in Assessing Patients with Recent Onset Chest Pain A Study in Tertiary Care Hospital, Dhaka Bangladesh - Roy, Udoy Shankar; Khan, Md Murshidur Rahman; Bhowmik, Tapas Kanti; Sarker, Ramendra Nath (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Chest pain or discomfort caused by acute coronary syndrome (ACS) or angina has a potentially poor prognosis, emphasizing the importance of prompt and accurate diagnosis. To evaluate a clinic set up specifically to assess patients with recent onset chest pain, particularly those presenting with a normal resting electrocargram. Method: The cross-sectional study was carried out from September 2016 to August 2017 in cardiology department of Shaheed Suhrawardy Medical College hospital, Sher-E-Bangla Nagar, Dhaka. Total 1000 consecutive patients with recent onset chest pain were evaluated within 24 hours of general practitioner referral, to find out the clinical diagnosis and management. Results: Total 1000 patients (535 men and 465women, mean age 51.5±11.4 years with range from 32 to 70 years) were assessed over 12 months. Most of the patients 844 (84.4%) had symptoms in duration of ≤30 days. Majority 433 (43.3%) patients had peptic ulcer disease (PUD), 317 (31.7%) patients had chronic stable angina (CSA), 94 (9.4%) had unstable angina (UA), 92 (9.2%) had anxiety neurosis (AN) and 64 (6.4%) had myocardial infarction (MI). Regarding outcome of the patients 525 (52.5%) [PUD: 433+ AN: 91] patients considered to have noncardiac pain and referred to medicine outpatient department (OPD) without further follow up. In a further 317 patients (31.7%, CSA) arrangements were made for outpatient review. Ninety four patients (9.4%, UA) were referred to National Institute of Cardiovascular diseases (NICVD) for admission out of them 61 patients were admitted for medical treatment & 33 patients were discharged from emergency department whose troponin-I were negative. Remaining 64 (6.4%) acute MI patients were admitted into Coronary Care Unit (CCU) of NICVD, out of them 41 patients received streptokinase injection, 23 patients received Enoxaparin injection, after conservative treatment all patients were advised to do coronary angiography within 3 to 4 weeks. Among these 43 patients underwent coronary angiography within 4 weeks, 23 patients had coronary angioplasty, eleven patients had coronary bypass surgery and nine patients refused any intervention and discharged with medicine. Conclusion: This experience highlights the inadequacy of a routine electrocardiogram reporting service in patients with recent onset of chest pain. Clinical diagnosis found were peptic ulcer disease (PUD), chronic stable angina (CSA), unstable angina (UA), anxiety neurosis and myocardial infarction (MI). Regarding outcome of the patients were coronary angiography followed by coronary angioplasty, coronary artery bypass surgery, discharged with medicine and referred to out patients department of medicine unit. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 65-68